METHODOLOGY OF TEACHING A FOREIGN LANGUAGE TO DIFFERENT AGES (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article explores effective methodologies for teaching foreign languages to learners of different age groups. It examines age-related cognitive, psychological, and social factors that influence language acquisition and discusses appropriate teaching methods for young children, adolescents, and adults. The study highlights the importance of age-specific approaches to enhance motivation, retention, and overall language proficiency.